Requirements for Organic Cotton Growing - Atabayeva Ma’muraxon; Toʻlanova Gulbahor Mahmudbek qizi (American Journal of Biology and Natural Sciences, 2024)
organic cotton is considered a pure environmental product. It is grown without chemical preparations, and the environment is not harmed even when grown completely harmless to human health.